2019
DOI: 10.3389/fonc.2019.00706
|View full text |Cite
|
Sign up to set email alerts
|

The Yin and Yang of Cytoreductive SBRT in Oligometastases and Beyond

Abstract: Background: Oligometastatic disease has emerged as a possibly distinct metastatic phenotype in numerous cancer histologies. With the advancement in treatment modalities including stereotactic body radiation therapy (SBRT), certain patients may derive benefits from local ablative therapy. SBRT alone has already shown to have potential benefits in certain oligometastatic disease types. However, more understanding of the immunologic modulation and microenvironment is needed to guide which patients may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The effectiveness of SBRT on LC is clearly associated with a doseresponse correlation; higher biologically equivalent dose (BED) leads to better tumor control (71,72). For lymph node metastases, 5year LC rates of uterine, cervical, and ovarian cancer range from 70 to 97%, and favorable disease-free survival and overall survival are reported in retrospective series (64,68,70,(72)(73)(74)(75)(76)(77).…”
Section: Omrgrt In the Management Of Oligometastatic Lymph Node Metastases From Gynecologic Malignanciesmentioning
confidence: 99%
“…The effectiveness of SBRT on LC is clearly associated with a doseresponse correlation; higher biologically equivalent dose (BED) leads to better tumor control (71,72). For lymph node metastases, 5year LC rates of uterine, cervical, and ovarian cancer range from 70 to 97%, and favorable disease-free survival and overall survival are reported in retrospective series (64,68,70,(72)(73)(74)(75)(76)(77).…”
Section: Omrgrt In the Management Of Oligometastatic Lymph Node Metastases From Gynecologic Malignanciesmentioning
confidence: 99%
“…Other studies are investigating intratumoral virus injection together with radiotherapy for malignant gliomas or recurrent ependymomas [NCT02457845, NCT00634231], as well as adoptive cellular therapy with radiotherapy (with or without temozolomide) for patients with brainstem gliomas [NCT03396575]. Finally, based on pre-clinical and clinical data suggesting more robust systemic immune responses to combinations of focal radiotherapy and immunotherapy ( 107 – 113 ), a few early studies are evaluating this combination in extracranial solid tumors and lymphomas [NCT03445858].…”
Section: Role Of Radiotherapy With Advances In Targeted Systemic Therapiesmentioning
confidence: 99%
“…Several studies have suggested that the immune system plays an important role in the therapeutic effects of radiation by promoting tumor cell death in the radiation field (2,3). For example, in preclinical cancer models, the stimulation of granulocyte-macrophage colony formation after irradiation has been shown to promote the migration of myeloid-derived suppressor cells (MDSCs) into circulation and through inflamed tissues (4,5).…”
Section: Introductionmentioning
confidence: 99%